Reconstruction of precipitation and temperature with annual growth rings of the cypress Taxodium mucronatum (Taxodiaceae) in Coahuila, Mexico - Villanueva-Díaz, José; Martínez-Sifuentes, Aldo Rafael; Reyes-Camarillo, Fátima del Rocío; Estrada-Ávalos, Juan (Revista de Biología Tropical, 2021)
Abstract: Reconstruction of precipitation and temperature with annual tree-rings of the Mexican baldcypress (Taxodium mucronatum Ten.), in the Río Sabinas, Coahuila basin. Introduction: Dendroclimatic reconstructions in water-yield basins lacking hydroclimatic data, such as the Rio Sabinas is important to analyze its interannual and multiannual climatic variability. One of the species useful for this purpose is the Mexican baldcypress (Taxodium mucronatum Ten.), a long-lived species with well-defined rings, present along the riparian zone of the Rio Sabinas that constitutes a “proxy” of interannual and multiannual climate variability. Objective: develop a seasonal reconstruction of precipitation and maximum temperature, and to analyze the influence of global circulatory modes on the annual radial increase of the species. Methods: Increment cores of the Mexican baldcypress specimens were dated through dendrochronological techniques to produce a ring-width series. Climate gridded data from two databases were used to develop a response function analysis for climate reconstruction purposes. Results: A ring-width chronology of 218 years (1808–2018) was developed and used to develop a seasonal April-June precipitation and a mean June-July maximum temperature reconstruction. The driest period detected on the rainfall reconstruction occurred from 1815 to 1818 with 27.4 mm and a maximum temperature of 41.2 ° C; while the wettest year was 1828 with 393.72 mm. The ring-width chronology was correlated with the SPEI and PDSI drought indices, and with indices of atmospheric phenomena such as El Niño Southern Oscillation, through the Southern Oscillation Index and the Multivariate Index; Pacific Decadal Oscillation, Atlantic Multidecadal Oscillation, monthly North American Monsoon System indices, and sea surface temperature. The relationship between the ring-width series and drought indices (SPEI, PDSI) was significant in June (r = 0.52, p <0.01), and June-August (r = 0.38, p <0.05) for the SPEI and reconstructed PDSI, respectively. It was found a significant association between the ring-width chronology and the reconstructed November-February SOI (r = -0.41, p < 0.01). The North American Monsoon System, Pacific Decadal Oscillation, and Atlantic Multidecadal Oscillation were not significant. Conclusions: On this study, we developed a climatic response function and reconstructed seasonal climatic variables (precipitation, maximum temperature) of importance to develop management strategies for conservation of the Mexican baldcypress on this basin, and to implement mitigation actions for the presence of extreme climatic events that may occur in the next coming years.